Narratives of Latin American Immigrant Media in Spain - Rodriguez Cánovas, Belen; Tufiño Murillo, Brenda Carolina; Guzmán Rincon, Alfredo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
Spain is a leading destination for migrants within the European Union, particularly from Latin America due to shared language and cultural proximity. The growth of the Latin American population has fostered the rise of ethnic media, coexisting with local outlets. These media flourished until 2008, influenced by the economic crisis, digital transformation, and the press downturn. It’s challenging to track these outlets, with only six remaining active in 2024. This research updates Latino-focused media in Spain, exploring their characteristics, narratives, and role in the daily lives of immigrants, revealing how they help preserve cultural identity and bridge two connected worlds.